The Impact of Work-Life Balance, Organisational Culture, and Job Involvement on Perceived Stress Among Academicians in Tamil Nadu - Mohideen , Mohamed; Kumar Katta, Ashok (Journal of Neonatal Surgery, 2025)
This study has investigated the direct and indirect relationships between Work-Life Balance and Organizational Culture on Perceived Stress, with Job Involvement as a proposed mediator, among 271 academicians in Tamil Nadu. A cross-sectional design was employed, utilizing standardized questionnaires, and data were analyzed using regression and PROCESS macro Model 4. The regression analysis revealed a significant overall model for Perceived Stress, with a positive direct effect of Work-Life Balance. While Organizational Culture was positively associated with Job Involvement, mediation analyses indicated that Job Involvement did not significantly mediate the effects of either Work-Life Balance or Organizational Culture on Perceived Stress. These findings suggest a complex interplay of these factors in predicting stress among academicians in this context, highlighting the need for further research to understand the underlying mechanisms and inform targeted interventions.